Endoscopic cyclophotocoagulation versus second glaucoma drainage device after prior aqueous tube shunt surgery. (2nd October 2016) - Murakami, Yohko; Akil, Handan; Chahal, Jasdeep; Dustin, Laurie; Tan, James; Chopra, Vikas; Francis, Brian
Abstract: Background: To evaluate the efficacy in controlling intraocular pressure (IOP) with endoscopic cyclophotocoagulation (ECP) versus implantation of a second glaucoma drainage device (GDD‐2) in the treatment of uncontrolled glaucoma with a prior aqueous tube shunt. Design: A nonrandomized retrospective chart review. Participants: Patients with refractory glaucoma following a failed initial tube shunt (Baerveldt Glaucoma Implant 350), who underwent ECP or GDD‐2 with Baerveldt Glaucoma Implant as a second surgery. Twenty‐five eyes underwent ECP, and 48 eyes received a GDD‐2. Methods: ECP or second tube‐shunt surgery. Main Outcome Measures: Reduction in IOP and antiglaucoma medications, and Kaplan–Meier survival with success defined as lOP ≥ 5 mmHg and ≤ 21 mmHg and ≥ 20% reduction from preoperative IOP. Secondary outcome measures were visual acuity and the presence of any postoperative complications. Results: Both ECP and GDD‐2 significantly lowered IOP (Student's t test) and number of antiglaucoma medications (Wilcoxon paired signed rank test). There were no significant differences in postoperative IOP (Student's t test) or antiglaucoma medications (Mann Whitney test) between ECP and GDD‐2 at 6 and 12 months. There was also no difference in the Kaplan–Meier survival outcomes between the two groups. Conclusion: Both ECP and GDD‐2 are both effective as second surgeries for refractory glaucoma that has failed a prior aqueous shunt.